Unele considerațiuni privind liberarea de răspundere penală a minorilor - Russu, Valentina (CEP USM, 2024)
Preventing and combating juvenile crime continues to remain a priority within the criminal policies of states, a fact determined by the specific features of juvenile delinquency. The international standards in the field of juvenile justice direct the states towards a policy focused on preventive measures, and the bringing of the minor to criminal responsibility and the application of punishments should be done only when the purpose of the criminal law cannot be achieved by using coercive measures of an educational nature. In this scientific approach, the author argues the importance of the institution of the release of minors from criminal liability, identifies the particularities and specific conditions of application.
Keywords: minor; criminal liability; răspundere penală